SISTEM APLIKASI PENGOLAHAN DATA KEPEGAWAIAN DI KECAMATAN MESTONG JAMBI - Yeni Nurjani (JURNAL AKADEMIKA)
Data accredited processing applications on Mestong village is an application that can simplify the processing of the data recipients of this aid kepegawaian. This application is to facilitate pengiputan the data, and to reduce the risk of errors, mistakes, and the difference in making the report so as to make the job faster and more efficiently. Making these applications using Borland Delphi 7.0 as a display interface, Microsoft acces to the processing of data and the database, as well as for making this application is the making of an application system data resident health card recipients for the poor. The conclusion reached by the author in making this application is making this application is the making of an application system data resident health card recipients for the poor, to reduce the risk of errors in proes storage and data writing, to optimize data collection and recording of population growing body forward, mempelancar effectiveness employee / I in the manufacture and processing of data gaji, data pegawai, can mempelancar the system work and to assist in making the report in order to more quickly and accurately.